Implementasi SCRUM pada Pengembangan Aplikasi Sistem ADI STETSA SMAN 4 Malang : Bidang Sarana Prasarana - Kevin Raihan; Aji Wibawa; Ilham Zaeni; Afifah Salim (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2021)
Educational facilities and infrastructure are all equipment/facilities used in the learning process to achieve educational goals. Educational facilities and infrastructure have a function to support the learning process carried out by students and teachers in the classroom. Management of educational facilities and infrastructure is a management activity that begins with planning needs, procurement, inventory, storage, school maintenance efficiently and on target. An example of the implementation of facilities and infrastructure management activities is at SMAN 4 Malang, where the facilities and infrastructure management activities carried out are data collection of goods and rooms catalogs as well as data collection of borrowed goods and rooms. Management of facilities and infrastructure at SMAN 4 Malang is difficult because of the large amount of data that must be managed. The development of the ADI STETSA Information System (Digital Application Studium Et Sapientia) for SMAN 4 Malang was developed using the SCRUM method because in this method everyone can adaptively overcome complex problems while productively and creatively producing high-value products. The process of developing the ADI STETSA information system was carried out in 5 sprints. The resulting information system can be used for infrastructure services at SMAN 4 Malang. Sarana dan prasarana pendidikan adalah semua perlengkapan/fasilitas yang digunakan dalam proses pembelajaran untuk mencapai tujuan pendidikan. Sarana dan prasarana pendidikan memiliki fungsi untuk mendukung proses pembelajaran yang dilakukan siswa dan guru di dalam kelas. Pengelolaan sarana dan prasarana pendidikan merupakan kegiatan manajemen yang dimulai dengan perencanaan kebutuhan, pengadaan, inventarisasi, penyimpanan, pemeliharaan sekolah secara efisien dan tepat sasaran. Contoh pelaksanaan kegiatan pengelolaan sarana dan prasarana terdapat di SMAN 4 Malang, dimana kegiatan pengelolaan sarana dan prasarana yang dilakukan adalah pendataan katalog barang dan ruangan serta pendataan barang dan ruangan yang dipinjam. Pengelolaan sarana dan prasarana di SMAN 4 Malang sulit dilakukan karena banyaknya data yang harus dikelola. Pengembangan Sistem Informasi ADI STETSA (Aplikasi Digital Studium Et Sapientia) untuk SMAN 4 Malang dikembangkan dengan menggunakan metode SCRUM karena dalam metode ini setiap orang dapat secara adaptif mengatasi masalah kompleks sambil secara produktif dan kreatif menghasilkan produk bernilai tinggi. Proses pengembangan sistem informasi ADI STETSA dilakukan sebanyak 5 sprint. Sistem informasi yang dihasilkan dapat digunakan untuk layanan sarana prasarana di SMAN 4 Malang.